God''s Ways with the World : Thinking and Practising Christian Faith. - Hardy, Daniel (Bloomsbury Publishing, 2005)
This book is devoted to recovering the truth and vitality of Christian faith by attempting to trace the ways of God with the modern world. Professor Hardy contends that the profundity of God''s interaction with the world, despite centuries of valuable contemplation, can best be understood by addressing those aspects of human thought which often give modern life its vitality. These are the very features with which theology has tended to lose touch, but which here are explored as areas in which the character and purposes of God may be manifest. Following the example of the great eras of theologi.